Position‐specific 15N isotope analysis in organic molecules: A high‐precision 15N NMR method to determine the intramolecular 15N isotope composition and fractionation at natural abundance. (17th July 2019) - Joubert, Valentin; Silvestre, Virginie; Lelièvre, Maxime; Ladroue, Virginie; Besacier, Fabrice; Akoka, Serge; Remaud, Gérald S.
Abstract: The position‐specific 15 N isotope content in organic molecules, at natural abundance, is for the first time determined by using a quantitative methodology based on 15 N Nuclear Magnetic Resonance (NMR) spectrometry. 15 N NMR spectra are obtained by using an adiabatic "Full‐Spectrum" INEPT sequence in order to make possible 15 N NMR experiments with a high signal‐to‐noise ratio (>500), to reach a precision with a standard deviation below 1‰ (0.1%). This level of precision is required for observing small changes in 15 N content associated to 15 N isotope effects. As an illustration, the measurement of an isotopic enrichment factor ε for each 15 N isotopomer is presented for 1‐methylimidazole induced during a separation process on a silica column. The precision expressed as the long‐term repeatability of the methodology is good enough to evaluate small changes in the 15 N isotope contents for a given isotopomer. As observed for 13 C, inverse and normal 15 N isotope effects occur concomitantly, giving access to new information on the origin of the 15 N isotope effects, not detectable by other techniques such as isotope ratio measured by Mass Spectrometry for which bulk (average) values are obtained. Abstract : The determination of the position‐specific 15 N isotope content, at natural abundance, is for the first time accessible by using quantitative 15 N NMR spectrometry. As an illustration, the isotopic enrichment factor for each 15 N isotopomer associated to the fractionation induced during separation on silica column of 1‐methylimidazole was measured.